Pelatihan Perencanaan Keuangan Keluarga Indonesia (PK2I) di GKAI Gading Serpong, Tangerang - Imanuel Adhitya Wulanata Chrismastianto; Wahyu Irawati; Ashiong P. Munthe; Lastiar R. Sitompul; Kristin Armis Pasaribu; Damai Yanti Manalu (Institute for Research and Community Services, 2023)
The situation analysis in community service of Gereja Kristen Alkitab Indonesia (GKAI) Gading Serpong shows that their daily living costs allocation tends to be disproportionate because they spend more than they earn, causing them difficulties in planning the income they get every month. Furthermore, the disproportion results in economic problems and conflicts in the family. Therefore, PkM activities, through the implementation of PK2I, that can provide real solutions to address family economic problems are needed. It is hoped that the program can support the realization of a happy and prosperous family now and in the future. PK2I was conducted in form of face-to-face training with 20 participants, implementing health protocols to prevent Covid-19 in GKAI Gading Serpong, Tangerang. The implementation of PkM activities in the first session was about the explanation of financial planning concept and its importance for today's families. The session was then followed by PK2I simulations using simulation sheets. In this session, participants were accompanied by direct assistants. The recapitulation results of post-training evaluation form show that PkM activities in PK2I training have met the objectives and were able to provide significant benefits for all participants.